The Heterogenous Effect of COVID-19 on Liver Transplantation Activity and Waitlist Mortality in the United States - Yuan, Qing; Haque, Omar; Coe, Taylor M.; Markmann, James F. (Frontiers in Surgery, 2021)
Background: The COVID-19 pandemic curtailed the practice of liver transplantation (LT), which lacks a temporizing life-saving measure for candidates on the waitlist. Aims/Objectives: The objective of this research was to (1) determine the effect of decreased LT activity on waitlist mortality in the United States and (2) assess if this effect was homogenous across the country. Methods: We conducted a retrospective, cross-sectional analysis utilizing United Network for Organ Sharing (UNOS) data assessing 3,600 liver transplants from January 1, 2020 to June 2, 2020. COVID-19 incidence data was taken directly from the New York Times case count. Results: During weeks 10 to 15 of 2020, there was a 38% reduction in the number of LTs performed nationally, which was temporally associated with a transient 97% increase in waitlist mortality. When stratified by UNOS region, waitlist mortality was inversely correlated with the number of LTs performed in all 11 regions. However, the range of the association strength (r) was large (Pearson correlation coefficient range: - 0.73 to - 0.01). Conclusion: Interruptions in LT activity due to COVID-19 were associated with rapid increases in waitlist mortality, and these effects were unevenly distributed among candidates across the United States. The transplant community can utilize these results to mitigate inequalities in transplant allocation between UNOS regions and advocate for the uninterrupted practice of LT should another pandemic surge or COVID-19 variant arise.